Burden, Differential and Causes of Child Mortality in India (2010–2020): A Review - Aninda Debnath; Chandrakant Lahariya (Preventive Medicine: Research & Reviews)
This review analyses the trends, prevalence, causes and disparities of child mortality in children up to 5 years of age in India using the latest data from the Sample Registration System and the National Family Health Survey. In 2020, approximately 26.1 million births and 0.84 million child deaths were estimated in India, with neonatal mortality accounting for 63.5% of all child deaths under five years of age. 60% of child deaths occurring in Uttar Pradesh, Madhya Pradesh, Bihar and Rajasthan. The analysis highlights that despite substantial reductions in the under-five mortality rate (U5MR) and infant mortality rate (IMR) from 1970 to 2020, the current rate of reduction is insufficient to meet the Sustainable Development Goals (SDGs) by 2030. In 2020, India achieved a U5MR of 25/1000 live births, with IMR, neonatal mortality rate (NMR) and early NMR at 28, 20 and 15/1000 live births, respectively. Rural areas and lower socioeconomic groups exhibit higher mortality rates, underscoring the need for targeted interventions. The primary causes of death include prematurity, low birth weight, pneumonia and birth asphyxia. To meet SDGs, India required an accelerated annual reduction rate of 2.1% for U5MR and 4% for NMR. The review underscores the need for high-impact interventions, especially in high-burden states and districts, to further reduce child mortality and ensure equitable health outcomes across the nation.